ANALISIS KEMAMPUAN LITERASI SAINS PADA ASPEK PENGETAHUAN DAN PROSES SAINS SISWA PADA MATERI WUJUD BENDA - Indah Febriana; Ronal Oktavianus; Millatin Hanifah; Ade Lia Norma Agustina; Ashlih Wilda; Ulin Fatimatuz Zahro; Farah Hilyana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Scientific literacy refers to the ability to utilize scientific knowledge, identify questions, and draw conclusions from facts to comprehend the universe and make decisions related to changes triggered by human activities. The importance of scientific literacy for students lies in its role as a key to continuing scientific learning. With a command of scientific literacy, students can comprehend various issues such as the environment, health, economics, and other problems within modern society closely tied to technology and advancements in scientific knowledge. This study aims to assess the mastery of scientific literacy in the aspects of knowledge and scientific processes among 4th-grade students at SDN 4 Karangbener. The research sample consisted of 17 randomly selected students. The research findings indicate that the scientific literacy skills of 4th-grade students are still relatively low, with an average score of 52.6 in terms of the knowledge aspect.